Captain underpants and the invasion of the incredibly naughty cafeteria ladies from outer space eaudiobook - Pilkey, Dav (Captain Underpants, 2018)
Alien lunch ladies attack in the third book in this #1 New York Times bestselling series by Dav Pilkey, the author and illustrator of Dog Man! George and Harold have played a trick or two on nearly everyone at Jerome Horwitz Elementary. When their latest prank causes the school's cranky cafeteria ladies to quit, Mr. Krupp hires a trio of unusual replacements — who happen to look an awful lot like aliens! Will that curtain-caped crusader, Captain Underpants, save the day once more? Or will those outer-space cafeteria ladies have him for lunch?